South-South trade liberalisation and shipping geography: a case study on India, Brazil, and South Africa. (1st January 2012) - Lee, Tsung-Chen; Lee, Paul T.W.
Freer South-South trade has been recognised as a vital engine for the developing countries to reap the maximum economic gains from multilateral trade liberalisation. One of the latest developments which draws considerable attention is the proposed free trade agreement among India, Brazil, and South Africa, namely IBSA, given the fact that the three countries are amongst the leading economies in the continents of South Asia, South America, and Africa, respectively. This paper applies a global computable general equilibrium model, Global Trade Analysis Project, and a converting approach to quantify the impacts of the IBSA trade liberalisation on seaborne cargo volumes. The major advantage of the GTAP model is that it can capture the effects of economy wide adaptation and asymmetric structure change in exports and imports caused by trade liberalisation. Based on our numerical results, removing high tariffs in the South-South trading routes reduces the significance of geographical distance in determining South-South trade patterns, and promotes distant trade with faraway countries.